PENGARUH KECANGGIHAN TEKNOLOGI INFORMASI, PERLINDUNGAN SISTEM INFORMASI. DAN KEMAMPUAN TEKNIK PEMAKAI SISTEM INFORMASI AKUNTANSI TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANASI PADA INDUSTRI JASA PERHOTELAN DI BANDA ACEH - Lilis Setiawati; Dinaroe Dinaroe (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
This study aims to determine the effect of information tecnology sophistication,information system protection, and user technical abability accounting information systems on the effectiveness of accounting information systems on the effectiveness of accounting information systems in the hospitality service industry in Banda Aceh. The population in this research is the hotel service industry in Banda Aceh, which consists of 14 hotels. The method in this study uses quantitative research methods with primary data obtained by questionnaires measured using a Likert scale. The sampling technique in this study was to use purposive sampling. With a total of 59 respondents. Multiple linear regression analysis techniques with SPSS 22. The results in this study indicate that : (1) The sophistication of information technology has a positive and significant effect on the effectiveness of accounting systems. (2) Protection of accounting information systems has a positive and significant effect on the effectiveness of accounting information systems. (3) User technical ability of users of accounting information systems has a positive and significant effect on the effectiveness of accounting information systems. (4) Information technology sophistication, protection of information systems, and technical ability of users of accounting information systems together have a positive and significant effect on the effectiveness of accounting information systems.